Table of Content - - (Journal of Educational and Psychological Sciences, 2024)
Table of Content: 1. Developing Primary School Management in the Kingdom of Saudi Arabia based on Self-management: Proposed Model Prof. Fatima Abdullah Al-Bishr, Ibtisam Wajib Alotaibi, Sarah Abdullah Alsuwaie 2. The effect of different patterns of digital storytelling (visual and audio) on enhancing Imaginary capabilities and Creative thinking of science studies of the second grade Najma Nasser Salim Al-Jabri 3. Association between personality traits and psychological burnout among the Coaches of First-Class teams and Unions in Muscat Dr. Salim Mohammed Ali Al-Ghailani 4. The Effectiveness of the Reality Counseling Program in Improving the Self-Esteem of Adolescents from Divorced Families Dr. Hany Ibrahim Elshamy, Mohamed Kamal Abdelrahman, Mahmoud Abdelaziz Eliwa 5. Work rotation and its role in getting rid of job burnout as the administrative assistant in middle-stage schools at east of Jeddah Manal Jaza Alotaibi, Prof. Najat Mohammed Saeed Alsaigh 6. Exploring the Utilization of Artificial Intelligence on Educational Efficiency: A Case Study in Riyadh Mrs. Sarah Hamoud Al-Kahtani